KEPENTINGAN EKONOMI POLITIK ISLANDIA MEMPERTAHANKAN KERJASAMA EKONOMI DENGAN UNI EROPA MELALUI PERJANJIAN EUROPEAN ECONOMIC AREA (EEA) - Mardalena, Sukmika; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Economic cooperation between Iceland with regional organizations in Europe has been started since 1970, the relationship is marked by the merger of Iceland to the European Free Trade Area (EFTA), a free trade organization in Europe. In 1972, Iceland establish bilateral relations with the European Economic Citizens (before it became the EU) in which to discuss about the free trade agreement. This relationship is growing up in 1994, Iceland joined into an agreement European Economic Area (EEA). Through the EEA agreement, Iceland has access to the EU internal market, but as a consequence of Iceland is required to adopt EU regulations relevant to the internal market. This research will discuss why Iceland retains the EEA economic cooperation with the EU. This research used qualitative research methods that the source data is taken from books, journals, newspapers, internet, and previous research has relevant data with the title. The writer uses liberalism perspective and nation state level analysis. By using the concept national interest and theory of theory of international cooperation’s K.J Holsti. Iceland maintains the EEA agreement because of the economic and political interests. Economically EEA agreement Iceland expand the international market, increase exports and imports to EU countries and boost GDP growth. Political interests of Iceland is to provide access without having to become an official member of the European Union, to protect fisheries and agricultural controls.Keywords: National Interst, European Economic Area, European Union, Internal Market